Development of the LaComm 1.0, A French medical communication analysis software: A study assessing its sensitivity to change. Issue 2 (February 2017) - Gibon, Anne-Sophie; Durieux, Jean-François; Merckaert, Isabelle; Delvaux, Nicole; Farvacques, Christine; Libert, Yves; Marchal, Serge; Moucheux, Angélique; Slachmuylder, Jean-Louis; Razavi, Darius
Highlights: The LaComm 1.0 tool is sensitive to change. The LaComm 1.0 is a valid method to assess training effectiveness in French. The LaComm is based on literal transcripts. Future French CST programs should use the LaComm 1.0 to permit comparability between studies. Abstract: Objective: To test and compare the sensitivity to change of a communication analysis software, the LaComm 1.0, to the CRCWEM's using data from a randomized study assessing the efficacy of a communication skills training program designed for nurses. Methods: The program assessment included the recording of two-person simulated interviews at baseline and after training or 3 months later. Interview transcripts were analyzed using the CRCWEM and the LaComm 1.0 tools. Results: One hundred and nine oncology nurses (mainly graduated or certified) were included in the study. The CRCWEM detected 5 changes out of 13 expected changes (38%) (e.g., more open directive questions after training) and the LaComm 1.0, 4 changes out of 7 expected changes (57%) (e.g., more empathic statements after training). For open directive question, the effect sizes of the group-by-time changes were slightly different between tools (CRCWEM: Cohen's d   =  0.97; LaComm 1.0: Cohen's d  = 0.67). Conclusions: This study shows that the LaComm 1.0 is sensitive to change. Practice implications: The LaComm 1.0 is a valid method to assess training effectiveness in French. The use of the Lacomm 1.0 in future French communication skills training programs will allow comparisons of studies.